2000
DOI: 10.1074/jbc.m908846199
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Receptor 2-α Supports Cell Growth Both in Iron-chelated Cultured Cells and in Vivo

Abstract: In most cells, transferrin receptor (TfR1)-mediated endocytosis is a major pathway for cellular iron uptake. We recently cloned the human transferrin receptor 2 (TfR2) gene, which encodes a second receptor for transferrin (Kawabata, H., Yang, R., Hirama, T., Vuong, P. T., Kawano, S., Gombart, A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
164
2
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(185 citation statements)
references
References 30 publications
11
164
2
5
Order By: Relevance
“…TfR2 is expressed almost exclusively in the liver, whereas TfR1, the classic receptor generally called TfR and expressed widely, is present in modest amounts in the liver. 8 Importantly, these related receptors appear to be regulated differently, stimulate distinct downstream effectors, and are internalized by distinct mechanisms. TfR1 is internalized by hepatocytes via a clathrin-dependent mechanism, whereas TFR2 localizes to lipid rafts and interacts with caveolin-1.…”
Section: Hepatic Endocytosis: There Is Still a Lot To Learnmentioning
confidence: 99%
“…TfR2 is expressed almost exclusively in the liver, whereas TfR1, the classic receptor generally called TfR and expressed widely, is present in modest amounts in the liver. 8 Importantly, these related receptors appear to be regulated differently, stimulate distinct downstream effectors, and are internalized by distinct mechanisms. TfR1 is internalized by hepatocytes via a clathrin-dependent mechanism, whereas TFR2 localizes to lipid rafts and interacts with caveolin-1.…”
Section: Hepatic Endocytosis: There Is Still a Lot To Learnmentioning
confidence: 99%
“…TfR2 differs from TfR1 in that it does not contain any iron-responsive elements in its mRNA, and its mRNA does not appear to be regulated by iron (10,19). Several studies have suggested that TfR2 is capable of binding transferrin, although with a reduced affinity (20,22,37). The role of TfR2 as a substitute for TfR1 in its absence is still elusive.…”
mentioning
confidence: 99%
“…TfR2 binds Tf in a pH-dependent manner, but its affinity for Fe 2 Tf (K D ϳ30 nM; Kawabata et al, 2000;West et al, 2000) is significantly lower than that of TfR1 (K D ϳ1 nM, Tsunoo and Sussman, 1983;Enns et al, 1991;Richardson and Ponka, 1997). Unlike TfR1, TfR2 expression is limited predominantly to hepatocytes (Kawabata et al, 1999;Fleming et al, 2000Fleming et al, , 2002Vogt et al, 2003;Calzolari et al, 2004;Zhang et al, 2004) and is not regulated by intracellular iron (Fleming et al, 2000;Kawabata et al, 2000Kawabata et al, , 2001. TfR2 cannot compensate for TfR1, whose knockout in mice results in embryonic lethality due to severe anemia (Levy et al, 1999).…”
Section: Introductionmentioning
confidence: 99%